Spatial and Temporal Analysis of Alphavirus Replication and Assembly in Mammalian and Mosquito Cells - Joyce Jose (American Society for Microbiology, 2017)
ABSTRACT Sindbis virus (SINV [genus Alphavirus, family Togaviridae]) is an enveloped, mosquito-borne virus. Alphaviruses cause cytolytic infections in mammalian cells while establishing noncytopathic, persistent infections in mosquito cells. Mosquito vector adaptation of alphaviruses is a major factor in the transmission of epidemic strains of alphaviruses. Though extensive studies have been performed on infected mammalian cells, the morphological and structural elements of alphavirus replication and assembly remain poorly understood in mosquito cells. Here we used high-resolution live-cell imaging coupled with single-particle tracking and electron microscopy analyses to delineate steps in the alphavirus life cycle in both the mammalian host cell and insect vector cells. Use of dually labeled SINV in conjunction with cellular stains enabled us to simultaneously determine the spatial and temporal differences of alphavirus replication complexes (RCs) in mammalian and insect cells. We found that the nonstructural viral proteins and viral RNA in RCs exhibit distinct spatial organization in mosquito cytopathic vacuoles compared to replication organelles from mammalian cells. We show that SINV exploits filopodial extensions for virus dissemination in both cell types. Additionally, we propose a novel mechanism for replication complex formation around glycoprotein-containing vesicles in mosquito cells that produced internally released particles that were seen budding from the vesicles by live imaging. Finally, by characterizing mosquito cell lines that were persistently infected with fluorescent virus, we show that the replication and assembly machinery are highly modified, and this allows continuous production of alphaviruses at reduced levels. IMPORTANCE Reemerging mosquito-borne alphaviruses cause serious human epidemics worldwide. Several structural and imaging studies have helped to define the life cycle of alphaviruses in mammalian cells, but the mode of virus replication and assembly in the invertebrate vector and mechanisms producing two disease outcomes in two types of cells are yet to be identified. Using transmission electron microscopy and live-cell imaging with dual fluorescent protein-tagged SINV, we show that while insect and mammalian cells display similarities in entry and exit, they present distinct spatial and temporal organizations in virus replication and assembly. By characterizing acutely and persistently infected cells, we provide new insights into alphavirus replication and assembly in two distinct hosts, resulting in high-titer virus production in mammalian cells and continuous virus production at reduced levels in mosquito cells—presumably a prerequisite for alphavirus maintenance in nature.